Hsa-miR-21-5p is induced by interleukin-6 and affects multiple pathogenic factors associated with fibroblast-like synoviocytes in rheumatoid arthritis - Kei Araki; Sho Mokuda; Hiroki Kohno; Naoya Oka; Hirofumi Watanabe; Michinori Ishitoku; Tomohiro Sugimoto; Yusuke Yoshida; Junya Masumoto; Shintaro Hirata (Scientific Reports)
Abstract Fibroblast-like synoviocytes (FLS) contribute significantly to the pathogenesis of rheumatoid arthritis (RA), particularly through their roles in synovitis and joint destruction. The microRNAs (miRNAs) are short non-coding RNA that regulate gene expression post-transcriptionally. Although more than 2000 human miRNAs are registered, comprehensive analyses of miRNA expression in FLS are limited. Herein, we investigated the relationship between miRNAs and FLS. Next-generation sequencing (small RNA-seq) was performed on primary cultured FLS derived from patients with RA to analyze the mature miRNA expression pattern. To assess inflammation-induced changes in miRNA levels, FLS were cultured with cytokines and evaluated by RT-qPCR. MiRNA mimics were transfected into FLS and an immortalized synovial fibroblast cell line (MH7A cells), and validated using conventional RNA-seq. Out of 2861 mature miRNAs, 297 mature miRNAs were detected and intronic miRNAs were predominated. Notably, hsa-miR-21-5p was abundantly expressed and its expression was enhanced by IL-6 stimulation. The induction of miR-21-5p mimic decreased the expression of Programmed Cell Death 4 (PDCD4) and Osteoprotegerin (OPG), while upregulating Semaphorin 5A (SEMA5A). MiR-21-5p mimic led to enhanced cell proliferation. These data suggest that hsa-miR-21-5p in FLS may exacerbate the pathophysiology of rheumatoid synovitis by promoting FLS proliferation, highlighting its potential as a therapeutic target in RA.